Paradigm of Gender Inequality in Contemporary Art: The artistic process and the “supposed differentiation” - Monteiro, Ilda (2021)
This investigation is subjected to a study of the literature review of a theoretical nature, through which a generalized description of the topic is made. In a more restricted way, the assumptions and strategies, in the face of gender inequality, in the field of the arts, of the western world since its origin, were ana- lyzed. Over the centuries, this issue has been discussed in a problematic way in the face of the struggle for equal opportunities of gender in the artistic world. Although changes emerged in the second half of the 20th century (during the second wave of feminism) this discriminatory situation in the artistic sphere was notorious in society and in the world, with profound changes in social paradigms. This reality in the field of art was not indifferent to these changes, as it was ex- tremely affected by feminism, both at the level of production and in artistic theory, taking into account the strong impact that feminism had on changes in the subordinate position, to a higherhierarchicalplan.Thisstudydescribes a general and current panorama of the artistic aspect of discrimination against female artists and the means conveyed by them.